1992
DOI: 10.1002/ijc.2910510323
|View full text |Cite
|
Sign up to set email alerts
|

SOD2: A new type of tumor‐suppressor gene?

Abstract: The activity of superoxide dismutases (SOD) 1 and 2 was analysed in correlation with mRNA and chromosome content in 6 SV40-transformed (TF) and in non-transformed (NF) human fibroblast cell lines. Total SOD activity was fairly constant, whereas the ratio SOD2/SOD1 was much lower in TF than in NF. The decrease in SOD2 activity was correlated with a low mRNA content, and with the presence of various chromosomal rearrangements leading to deletions of the long arm of chromosome 6 where the gene is mapped. In contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
1
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(80 citation statements)
references
References 26 publications
4
74
1
1
Order By: Relevance
“…Bravard and colleagues first proposed MnSOD as a potential tumor suppressor gene that might also be involved in differentiation. 25 First evidences came from studies in immortal rat embryo fibroblasts that undergo spontaneous differentiation into muscle and adipose cells, process that is accompanied with a significant increase in MnSOD activity. 30 This phenomenon can be extended to some fungi in which MnSOD expression is also associated with both oval and falcate conidia differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bravard and colleagues first proposed MnSOD as a potential tumor suppressor gene that might also be involved in differentiation. 25 First evidences came from studies in immortal rat embryo fibroblasts that undergo spontaneous differentiation into muscle and adipose cells, process that is accompanied with a significant increase in MnSOD activity. 30 This phenomenon can be extended to some fungi in which MnSOD expression is also associated with both oval and falcate conidia differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…25 Given that melatonin is an antioxidant agent either as a direct scavenger or indirectly by modulating the expression of antioxidant enzymes or glutathione content, 26 we decided to study the levels of MnSOD in melatonininduced NE-differentiated cells and compared with control, nondifferentiated cells. MnSOD but not CuZnSOD immunoreactivity increased in NE-like differentiated cells, either with MEL, cs-FBS or with db-cAMP (Fig.…”
Section: Ne-like Cells Show Higher Levels Of Mnsodmentioning
confidence: 99%
“…[5][6][7] Collectively, these findings have led to the hypothesis that that MnSOD functions as a type of tumor suppressor gene. 8 Breast carcinoma cells and primary tumors generally have lower MnSOD expression and activity than their normal nontumorgenic counterparts. 3 However, the precise mechanism leading to the down regulation of MnSOD during malignant transformation is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the malignant phenotype is suppressed when MnSOD activity is elevated in certain cancer cells (Li et al, 1998a, b;Zhang et al, 1999). MnSOD has been implicated as a tumor suppressor and as a metastasis suppressor in some tumor cell lines (Oberley and Buettner, 1979;Oberley and Oberley, 1988;Bravard et al, 1992). MnSOD modulates the cellular redox environment by converting superoxide radical (O 2 À ) to H 2 O 2 and dioxygen.…”
Section: Introductionmentioning
confidence: 99%